La Monstruosité du discours direct : perspective diachronique - Élise LOUVIOT (E-REA)
Syntactically, a speech represented in direct style is often interpreted as the direct object of the speech verb. This paper examines some of the oldest and most archaic English texts available to us (a group of eight Old English poems) to determine whether such an interpretation is applicable to that corpus. The evidence suggests that such is not the case. Semantically, in early literate cultures, speech is not conceived as an object but as an event. Syntactically, speeches represented in direct style in Old English poetry often occur after intransitive speech verbs or speech verbs that already take another object. It seems that in Old English poetry at least, Direct Speech is true parataxis: the succession of two discourses without any syntactic integration.